Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Review Problem Set - Page 520: 39



Work Step by Step

Using the rule $\frac{a^{m}}{a^{n}}=a^{m-n}$, we obtain: $(\frac{6x^{\frac{2}{7}}}{3x^{-\frac{5}{7}}})^{3}$ =$(\frac{6}{3}\times\frac{x^{\frac{2}{7}}}{x^{-\frac{5}{7}}})^{3}$ =$(2\times x^{\frac{2}{7}-(-\frac{5}{7})})^{3}$ =$(2\times x^{\frac{2}{7}+\frac{5}{7}})^{3}$ =$(2\times x^{\frac{2+5}{7}})^{3}$ =$(2\times x^{\frac{7}{7}})^{3}$ =$(2x^{1})^{3}$ =$2^{3}x^{1\times3}$ =$8x^{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.